Konsep Pendidikan Ibnu Miskawih dan Relevansinya dengan Kurikulum Berbasis Cinta di Tingkat Madrasah Ibtidaiyah - maulana, M. Fahmi (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2026)
This study aims to analyze the conceptual relevance of Ibn Miskawayh's educational thought to the Love-Based Curriculum (KBC) at the madrasah level. The study focuses on the suitability of values, alignment of educational objectives, relevance of methods, and paradigmatic connectedness. This study uses a qualitative approach with a library research type. Data are sourced from Ibn Miskawayh's main works, especially Tahdzīb al-Akhlāq wa Taṭhīr al-A‘rāq, literature on the Love-Based Curriculum, and other relevant scientific sources. The results show a strong alignment between Ibn Miskawayh's concept of morality and love as the core value of the KBC in shaping students' personalities. This alignment is also evident in the educational goal, namely the formation of people with morals and loving character through the integration of intellectual, emotional, and moral dimensions. In addition, the principles of habituation, exemplary behavior, and moral experience in Ibn Miskawayh's thought are in line with the value of habituation and experiential learning approaches in the KBC. This study concludes that Ibn Miskawayh's educational thinking has strong conceptual and normative relevance to the Love-Based Curriculum paradigm as a humanistic educational model in the madrasa environment.